Prospects of the specialists’ preparation in the field of air and space law - Сопілко, Ірина Миколаївна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article focuses on the necessity for adequate training of the specialists in the field of air and space law. Theauthors emphasize that the scientific-practical conference not only determines the direction of new research in thisarea and identify gaps in the legislation, but also greatly improves the quality of legal education.